Insights into handling and delivery of Y-90 radioembolization therapies - Osborne, Dustin R.; Minwell, Gregory; Pollard, Bradley; Walker, Chris; Acuff, Shelley N.; Smith, Kristen; Green, Cain; Taylor, Rachel; Stephens, Christopher D. (Frontiers in Nuclear Medicine, 2023)
Introduction: The use of Y-90 radioembolization techniques has become a standard tool for the treatment of liver cancer and metastatic diseases that result in liver lesions. As there are only two approved forms of radioembolization therapy, the procedures for use are also fairly standardized even though exact international and interdepartmental procedures can vary. What has been less published over the years are the nuanced differences in delivery techniques and handling of the two available Y90 radioembolization therapies. This paper seeks to examine various aspects of delivery techniques, product handling, and radiation exposure that differ between the available and approved products. Understanding these differences can assist with providing more efficient treatment, confirmation of accurate therapy, more informed handling of the products, and improved training of physicians and other hospital staff. Conclusion: Although glass and resin radioembolization therapies are similar, they both have unique characteristics related to their administration and handling by staff. Understanding the nuances can assist in providing more efficient delivery, better staff education, and reducing radiation exposure to everyone involved with these therapies. The use of near real-time monitoring is feasible and can be used to obtain critical information about the delivery success of a therapy and can inform physicians on their techniques to optimize their practice as well as provide more consistent training to residents.